Applications of biological flocculants (BFs) for coagulation treatment in water purification : turbidity elimination - Ma, F. (Array, 2008)
Summary: In this study, coagulation performance by using biological flocculants (BFs; produced from strain Bacillus sp. F6) for turbidity removal was investigated. The results demonstrated that BFs were able to eliminate turbidity from kaolin clay solution over a wide dosage range (γDR = 6-20 mg L-1). The removal efficiency with BFs reached 86 % on average, lower than 95 % with Al2(SO4)3 (γAl = 6.5 mg L-1) and 96 % with Fe2(SO4)3 (γFe = 10 mg L-1), respectively. For bioflocculants, bridging flocculation other than charge neutralization should be responsible for turbidity removal. The combined applications of BFs with Al2(SO4)3 (ζAl/BF = 0.33) and Fe2(SO4)3 (ζFe/BF = 0.05) increased overall turbidity removal up to 97 %. It was also shown that combination of BFs and Fe2(SO4)3 was effective for removing turbidity from raw water. This study provides a proof-in-concept demonstration of BFs for water purification, which can in part reduce operational costs in coagulation treatment, as well, effectively reduce the concentration of residual metallic elements (e.g. aluminum) in coagulated solution